Travel advice for the immunocompromised traveler: prophylaxis, vaccination, and other preventive measures [Corrigendum] - Patel RR; Liang SY; Koolwal P; Kuhlmann FM (Dove Medical Press, 2015)
Patel RR, Liang SY, Koolwal P, Kuhlmann FM. Therapeutics and Clinical Risk Management. 2015;11:217–228.On page 224, Meningococcal vaccine heading, second sentence “Vaccination is recommended with the quadrivalent polysaccharide (Menactra™)” should have read “Vaccination with the quadrivalent meningococcal conjugate vaccine (MCV4) is recommended”. Read the original paper